2022
DOI: 10.3390/app122211471
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Conversions of Mizithra Second Cheese Whey by Wild-Type Non-Conventional Yeast Strains: Production of Yeast Cell Biomass, Single-Cell Oil and Polysaccharides

Abstract: The cultivation of oleaginous yeasts on various agro-industrial residues and the subsequent production of microbial lipids (single-cell oils), which can be used as starting materials for the synthesis of both “second generation” biodiesel and various types of oleochemicals, is considered as one of the most important approaches of the Industrial Biotechnology, in terms of circular economy and green and sustainable development. In this study, seven wild-type non-conventional yeast strains were evaluated for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Analyses performed by ASG Analytik-Service AG (Neusäss, Germany) indicated that the glycerol content was 74.9%, the water content was 11.8%, the ash content was 3.4%, the methanol content was 2.05% and the non-glycerol organic matter content was 9.9%. The initial pH value was set at 7.2 ± 0.1, and pH adjustment, when necessary, was performed as in Vasilakis et al [ 22 ]. The main culture was inoculated after sterilization (121 °C, 20 min); the strains were derived from the pre-culture (ranging between 0.5 and 10% of the working fermentation volume) when the cell growth was in the exponential phase.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses performed by ASG Analytik-Service AG (Neusäss, Germany) indicated that the glycerol content was 74.9%, the water content was 11.8%, the ash content was 3.4%, the methanol content was 2.05% and the non-glycerol organic matter content was 9.9%. The initial pH value was set at 7.2 ± 0.1, and pH adjustment, when necessary, was performed as in Vasilakis et al [ 22 ]. The main culture was inoculated after sterilization (121 °C, 20 min); the strains were derived from the pre-culture (ranging between 0.5 and 10% of the working fermentation volume) when the cell growth was in the exponential phase.…”
Section: Methodsmentioning
confidence: 99%
“…Some manuscripts are related to the use of SCW as a biotechnological substrate for probiotic or starter cultures [ 18 , 19 , 20 ]. Others refer to its potential to produce biofuel products [ 21 , 22 , 23 ]. The use of SCW to produce fermented drinks or as an ingredient in food formulations, was also evaluated [ 3 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, various strategies have been adopted attempting to manage SCW due to the restrictions and the demanding economic costs of its disposal. Although not so widely investigated as cheese whey [3,4], a literature review related to SCW revealed it is mainly exploited as a fermentation medium for the sustainable generation of added-value products, including biofuels [5], eco-friendly bioplastics (e.g., polyhydroxyalkanoates) [6,7] and polysaccharides, as well as for biomass production [8,9]. In addition, SCW seems to offer a promising alternative source for the development of innovative food products such as probiotic drinks [5] and vinegar [6].…”
Section: Introductionmentioning
confidence: 99%